Enhancing soil properties and barley yield using organic amendments in a semi-arid Algerian steppe - Abderrazak, Mabrouki; Hiouani, Fatima; Ouali, Abdelouahad; Djamila, Madani (Journal of Water and Land Development, 2026)
Sustainable management of soils with low organic matter in semi-arid regions remains a major agricultural challenge. Organic amendments can improve soil structure and increase productivity. This study evaluated the effects of poultry manure (PM) and palm compost (PC) on soil physical properties at two depths (0–20 cm and 20–40 cm) and on the yield of barley (Hordeum vulgare L. ‘Rihane 03’) in El-Maadher, Algeria. A randomised complete block design with three replications was used, comprising three treatments: T1 (control), T2 (PM), and T3 (PC). The amendments significantly improved soil physical properties, with the effects most pronounced in the 0–20 cm layer. At maturity, PM reduced bulk density by 7% and increased porosity by 15% and permeability by 82% compared with the control. PC also improved these properties, although it was less effective than PM. Both amendments significantly (p < 0.05) increased yield components. PM produced the highest grain yield (11.2 Mg∙ha−1), followed by PC (9.8 Mg∙ha−1), both of which were considerably higher than the control (5.3 Mg∙ha−1). Overall, the study indicates that poultry manure is the most effective organic amendment for improving soil hydro-physical properties and increasing barley yield. These findings highlight the importance of selecting appropriate organic amendments to achieve successful agricultural outcomes. For farmers, the results provide a clear, evidence-based recommendation: poultry manure can deliver rapid soil improvement and maximise productivity. This research presents a practical approach to advancing sustainable agriculture in semi-arid areas by enhancing soil health, improving water-use efficiency, and contributing to food security.